Optimisation in water absorption of low molarity seawater and zeolite based geopolymer foam reinforced with nanocellulose - T., Chai Hua; M., Norkhairunnisa; Wayayok, A.; M. Basri, M. S.; Al Bakri Abdullah, M. M. (Institute of Metallurgy and Materials Science of Polish Academy of Sciences, Committee of Materials Engineering and Metallurgy of Polish Academy of Sciences, 2024)
The aim of this study is to optimize the composition of geopolymer foam that leads to the highest water absorption. This study utilized Response Surface Methodology to analyze the relationship between factors (Seawater/Potassium Silicate, Potassium Hydroxide/Potassium Chloride, Sodium Laureth Ether Sulfate/Benzalkonium Chloride and Hydrogen Peroxide/Nanocellulose and its response (water absorption). The concentration of the alkaline solution is maintained at a low level of Molar Ratio 2.01-2.53. It was found that all factors are significant with ρ-value<0 except for KOH/KCl with ρ<0.581. The highest water absorption by geopolymer measured is 35 , in the middle range of all factors. Simple water immersion of 30 days shows no significant physical changes on the geopolymer, proving its rigidity under water.